Isolation and characterization of amber mutations in the lexA gene of Escherichia coli K-12. - Pacelli, L Z (1979)
We describe the isolation and characterization of amber mutations in the lexA gene of Escherichia coli K-12. These mutations, designated spr(Am), were isolated and characterized in a lexA tif sfi genetic background. They abolished the sensitivity of the strain to UV light and resulted in high rates of synthesis of recA protein. Phage lambda+ failed to lysogenize the strains as observed with similar strains carrying non-amber spr mutations described previously, thereby indicating a constitutive expression of the phage induction pathway. Introduction of an amber suppressor mutation into a strain bearing the spr(Am) mutation restored expression of the LexA mutant phenotype. We conclude that spr mutations either inactivate or prevent synthesis of the lexA gene product and that loss of this product results in constitutive expression of the E. coli induction system in the tif sfi genetic background.